Effects of nifedipine on endothelial function, assessed by flow-mediated vasodilatation in pregnant patients. (12th December 2022) - Grin, Leonti; Laish-Farkash, Avishag; Bruoha, Sharon; Rabinovich, Mark; Harlev, Avi; Anteby, Eyal; Yosefy, Chaim; Shenhav, Simon
Abstract: Objectives: To evaluate the endothelial function, through flow-mediated vasodilation parameters from brachial artery test in women receiving nifedipine for acute tocolysis with threatened preterm delivery. Methods: In a prospective study in a university-affiliated hospital, each participant served as herself control. We evaluated various parameters of endothelial function in 22 patients between 27 and 33 weeks of gestation with a diagnosis of threatened preterm delivery (TPTD) before and after 48 h of nifedipine treatment. Each patient received 80 mg nifedipine per day. The assessment tool was Brachial artery reactivity test (BART). Primary outcome was flow mediated vasodilation (FMD). Results: The average participant's age was 27 ± 4.5 years, median gestational age of 28.5 weeks, BMI, kg/m 2 (mean ± SD) 28.4 ± 3.3. Systolic blood pressure (mmHg) and diastolic blood pressure (mmHg) decreased from 108 ± 6 to 104 ± 5, p  < .001 and from 66 ± 4 to 63 ± 4, p  < .001, respectively. FMD (%) significantly decrease from 10.8 ± 6.1 to 7.2 ± 4.7, p  = .03 prior to and after nifedipine treatment. The basal brachial artery diameter (mm) at rest was (3.19 ± 0.38 versus 3.39 ± 0.49, p  = .28) before versus after nifedipine. The largest brachial artery diameter (mm) was (3.54 ± 0.35 versus 3.58 ± 0.44, p  = .76) before versus after nifedipine. Conclusions: Our results suggest unfavorable changes in FMD probably as a result of nifedipine used for acute tocolysis. Future prospective studies should try to evaluate the safety of acute and maintenance tocolytic therapy with nifedipine on endothelial function in pregnant women.